Influences of the ecotourism industry in Mekong Delta – Vietnam: The mediating role of Tourist Satisfaction - Thanh Tiep Le (Cogent Business & Management, 2024)
The aim of this paper is to examine those factors that can affect the performance of the ecotourism industry in Vietnam. The well-known influencing and meditating factors are identified with strong connections in the ecotourism industry. Based on an extended literature review on travel service, safety and nature for tourist satisfaction, while the culture, facilities, native people, food, beverage and experience factors. The collected data was analyzed by using the structural equation system. The current work presents the exploratory survey with data collection technique through different surveys. One of the surveys relates to tourist destination and tourism companies in Mekong Delta. The tourist satisfaction has the strongest impact on the performance of ecotourism industry and has a strong impact to sustain the development of the ecotourism industry in Mekong Delta, Vietnam. The obtained results indicate that the impacts of travel service, safety and nature for tourist satisfaction, while the culture, facilities, native people, food, beverage and experience factors also play an important role in the tourist satisfaction. These findings indicate that by improving the performance of the ecotourism industry, the tourist satisfaction must be enhanced. To the best of our knowledge, these findings help the managers tourism sector, tourism companies, the local authorities, etc., to review the overall matrix to see the what and the how to enhance the performance of the ecotourism industry in Mekong Delta. Accordingly create the most suitable and practical policies and strategies for sustainable development of ecotourism industry in Mekong Delta.The tourist satisfaction has the strongest impact on the performance of ecotourism industry and has a strong impact to sustain the development of the ecotourism industry in Mekong Delta, Vietnam. The obtained results indicate that the impacts of travel service, safety and nature for tourist satisfaction, while the culture, facilities, native people, food, beverage and experience factors also play an important role in the tourist satisfaction. These findings indicate that by improving the performance of the ecotourism industry, the tourist satisfaction must be enhanced. Those findings help the managers tourism sector, tourism companies, the local authorities, etc., to review the overall matrix to see the what and the how to enhance the performance of the ecotourism industry in Mekong Delta. Accordingly create the most suitable and practical policies and strategies for sustainable development of ecotourism industry in Mekong Delta, Vietnam.
Keywords: 650; Eco-tourism; tourist satisfaction; sustainable tourism; ecotourism industry performance; Vietnam